Strategi Guru dalam Pengembangan Mutu Pembelajaran Berbasis Higher Order Thinking Skills Pada Mata Pelajaran Matematika - Sufa, Faila; Nikmah, Ulin; Rohim, Ahmad Abdul; Haq, Ahmad Khanif Izzul; Febrianti, Evita Nurma; Basyar, Mohammad Aniq Khoirul; Malihah, Zahlatul; Safira, Zona Nofiana (Sekolah Tinggi Agama Islam Pati, 2023)
The background of this research is to determine teacher strategies in developing the quality of HOTS-based learning in Mathematics Subjects. This research aims to 1) find out and explain teachers' strategies in developing the quality of HOTS-based learning in Mathematics Subjects in Class V 2) find out the supporting factors and inhibiting factors for teachers' strategies in developing the quality of HOTS-based learning in Mathematics Subjects in Class V. Data collection with interviews, observation and documentation. This research uses a historical approach. This qualitative research data analysis uses interactive analysis, namely data reduction, data display, and drawing conclusions. The research results show: 1) The teacher's strategy in developing the quality of HOTS-based learning is implemented in three stages: the planning stage, the teacher makes a Learning Implementation Plan with high- level thinking learning indicators: cognitive level (C4, C5 and C6). In the implementation stage, the teacher gives problems to students using video and LCD. The teacher applies the Problem Based Learning model where the teacher becomes a facilitator, while students are encouraged to solve problems. Teacher assessment stage: written test, description test and performance test. 2) Supporting factors: a) professional class teachers, b) the head of the madrasah carries out academic supervision activities, c) the availability of learning media and supporting tools, and d) the existence of regular coaching meetings once a month. 3) Inhibiting factors: a) limited allocation of learning time, b) differences in parenting styles for children at home, c) differences in students' ability to understand the material.